2007
DOI: 10.1177/001440290707300306
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Predictive of the Problem Behavior of Children at Risk for Emotional and Behavioral Disorders

Abstract: Logistic regression analyses were used to establish the most robust set of risk factors that would best predict borderline/clinical levels of problem behavior (i.e., a t score at or above 60 on the Child Behavior Checklist Total Problem scale) of kindergarten and first-grade children at risk for emotional and behavioral disorders. Results showed that among the 11 risk factor domains considered, 5 were most predictive of borderline/clinical levels of problem behavior: externalizing behavior pattern, internalizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 17 publications
4
44
0
3
Order By: Relevance
“…A study conducted by Briggs-Gowan et al (1996) revealed that there is a connection between the distress of a mother and the reporting of problematic behavior of girls. The results of this study seem to support their findings and imply that the reporting of a child's internalizing problems may be affected by the distress of parents (Abidin 1992;Costa et al 2006;Nelson et al 2007). …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A study conducted by Briggs-Gowan et al (1996) revealed that there is a connection between the distress of a mother and the reporting of problematic behavior of girls. The results of this study seem to support their findings and imply that the reporting of a child's internalizing problems may be affected by the distress of parents (Abidin 1992;Costa et al 2006;Nelson et al 2007). …”
Section: Discussionsupporting
confidence: 80%
“…Mothers' depression or parenting distress is factors that negatively affect the quality of parenting (Abidin 1992) and have been regarded as risk factors for children's development (Costa et al 2006;Nelson et al 2007). After evaluating 193 meta-analyses on mental illness during childhood, Goodman et al (2011) reported that a mother's depression leads to an increase in her child's negative behavior and was highly related not only with internalizing behavioral problems but also with externalizing behavioral problem.…”
Section: Depression In Mothers and Parenting Distressmentioning
confidence: 99%
“…Verifi cámos ainda uma associação positiva entre o Psicoticismo e os comportamentos problema, o que ilustra que os jovens com estes problemas têm maior tendência para apresentarem características de alienação social e da realidade, bem como bizarria no comportamento e suspeição em relação aos outros. Considerando a literatura, estes resultados apoiam os estudos que têm mostrado a associação entre problemas comportamentais, por um lado, e características como a impulsividade, desinibição, menor conscienciosidade e menor amabilidade, por outro (Barnown et al, 2005;Cukrowicz et al, 2006;Frick, 2004;Frick & Dantagnan, 2005;Hill, 2002;Joyce & Oakland, 2005;Latzam, Vaidya, Clark, & Watson, 2011;Lynam & Miller, 2004;Miller & Lynam, 2001;Nelson, Stage, Duppong-Hurley, Synhorst, & Epstein, 2007;Ruchkin et al, 2001;Singh & Waldman, 2010). Além disso, estes resultados obtidos com uma amostra de jovens sem sinalização psicopatológica vêm reiterar a importância que a investigação tem atribuído à personalidade na explicação e compreensão das alterações comportamentais (e da probabilidade da sua ocorrência) na adolescência (Gute & Eshbaugh, 2008;Hill, 2002;Joyce & Oakland, 2005;Miller & Lynam, 2001;Ruchkin et al, 2001).…”
Section: Discussionunclassified
“…Research reports that early problem behavior is related to poor school experiences; therefore, students with problem behaviors are likely to struggle early, often, and throughout their school careers and, in general, life Nelson et al, 2007;Stormont et al, 2005). Unfortunately, children at-risk for developing EBD frequently do not receive services until late elementary school ) when behavior problems have gotten worse and often are extremely difficult to correct (Walker et al, 2004).…”
Section: Early Interventionmentioning
confidence: 99%
“…Therefore, students faced with barriers to learning are likely to struggle early, often, and throughout their school careers and life Nelson, Stage, Duppong-Hurley, Synhost, & Epstein, 2007;Stormont, Lewis, & Beckner, 2005).…”
Section: Introductionmentioning
confidence: 99%